Cement solidification silt strength prediction method based on gel-air ratio
Through the cement-cured silt strength prediction method based on the glue-empty ratio, combined with the initial porosity, degree of hydration and volume expansion rate, the problem of insufficient accuracy in the prediction of unbounded compressive strength of improved soil in the prior art is solved, and efficient and accurate strength prediction is achieved.
Patent Information
- Application Number
- CN202411777058.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The prior art is difficult to effectively predict the unbounded compressive strength of improved soil, resulting in insufficient prediction accuracy and high cost in engineering practice.
By defining the glue-free ratio of cement-based material cured silt, a cured silt strength prediction formula is proposed with the glue-free ratio as the only variable, and combining the initial porosity, degree of hydration and volume expansion rate, rapid strength prediction for different proportions and different age periods is achieved.
This method can significantly improve the prediction accuracy of unlimited compressive strength of cement-based material cured silt, and obtain the fitting coefficient without pre-testing, which significantly improves the professionalism and efficiency of the prediction process.
Smart Images

Figure CN119757119A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for predicting the strength of cement-solidified silt based on the ratio of cement to air. Background Art
[0002] During the construction of urban infrastructure, excavated soil is often treated as waste, which is not only a huge waste of land resources, but also increases unnecessary construction costs due to the transportation and stacking of soil. In fact, if these soils can be used reasonably, they can play an important role in many fields. High-quality soil can not only be used as roadbed filling, but can also be effectively applied in many fields such as construction, environmental protection, and landscape design. For soils with poor engineering properties, such as silt, they can be converted into materials with practical value through proper pretreatment. For example, after silt is improved with cement-based materials, not only its strength is improved, but it can also be used in a variety of engineering structures, such as foundation treatment, dam construction, and land improvement.
[0003] Since factors such as moisture content, particle distribution and cement content of silt may vary significantly between different batches, these variables have a direct impact on the mechanical properties of improved soil. At present, the unconfined compressive strength test (UCT) is an important means to evaluate the engineering applicability of improved soil, but it has high requirements for experimental conditions and resources. In order to reduce experimental costs and improve prediction efficiency, it is particularly important to develop a numerical calculation method that can predict the unconfined compressive strength of improved soil. The application of this method is not limited to roadbed filling, but can provide efficient solutions for many fields such as construction, environmental remediation, and land development.
[0004] In engineering practice, digital design methods based on numerical calculation have shown their broad application prospects. However, traditional methods still have room for improvement in accuracy and applicability. Therefore, studying the strength prediction method of silt solidified by new cement-based materials can not only improve the accuracy of prediction, but also provide solid theoretical support for engineering practice, which has far-reaching significance. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a method for predicting the strength of cement-solidified silt based on the glue-air ratio. The method defines the glue-air ratio of cement-solidified silt, and proposes a strength prediction formula for solidified silt with the glue-air ratio as the only variable, which can realize rapid strength prediction under different mix ratios and different ages.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for predicting strength of cement-solidified silt based on the ratio of cement to air, the specific steps comprising:
[0008] Step 1, determining the specific gravity of the silt and the cement-based curing agent, and then calculating the initial porosity according to the mass, volume and mix ratio of the cured silt;
[0009] Step 2, conducting indoor experiments to determine the hydration degree of the cement-based curing agent at different curing ages, and recording the specific gravity at the corresponding curing age, and then calculating the volume expansion rate of the cement-based curing agent;
[0010] Step 3, substituting the calculated initial porosity, hydration degree and volume expansion rate into the calculation formula of the glue-void ratio, so as to obtain the glue-void ratio of cement-solidified silt at different curing ages;
[0011] Step 4: Substitute the cement-air ratio into the strength prediction model to predict the unconfined compressive strength of cement-solidified silt at different curing ages.
[0012] The strength prediction model is shown in the following formula:
[0013] q u =y0+A×e Bx
[0014] In the formula, y0, A, B are fitting parameters, q u represents the unconfined compressive strength of the solidified silt, and x represents the gel-spatial ratio GSR of the solidified silt;
[0015] The calculation formula of the glue-air ratio GSR is as follows:
[0016]
[0017] In the formula, m cd , W s (t), P and G cd are the amount of cement-based material added (kg), hydration degree (%), volume expansion rate (%) and specific gravity; g is the acceleration of gravity (9.8 m / s 2 ); n0 and V are the initial porosity (%) and volume (m 3 ), γ w is the density of water (kN / m 3 ).
[0018] Further, the hydration degree W s The determination method of (t) comprises the following steps:
[0019] Step 1: Mix the cement-based material with water according to the standard consistency and place it under standard curing conditions (temperature of 20±2°C and relative humidity of more than 95%) for 3, 7, 14, 28, 60 and 90 days;
[0020] Step 2: taking out the cement-based material that has reached the curing age, freeze-drying, crushing, and passing through a 2 mm sieve to obtain a sieved sample;
[0021] Step 3: Take 5g of sieved samples of different curing ages, place them in a muffle furnace at 1000℃ for 2 hours, cool them in a dry environment, and weigh the sample mass, recorded as m t , t is the curing age (t = 3, 7, 14, 28, 60, 90), then the weight of non-evaporated water of cement-based materials at time t is (5-m t ), the non-evaporable water content of cement-based materials at time t is defined as L t , calculated using the following formula:
[0022]
[0023] Step 4: Use the function shown in the following formula to calculate the non-evaporable water content L of cement-based materials at 6 curing ages. t (t=3,7,14,28,60,90) are fitted to obtain L t Nonlinear function of curing age t;
[0024]
[0025] Step 5: Use step 4 to get L t Regarding the nonlinear function of curing age t, the non-evaporable water content of cement-based materials when fully hydrated is predicted. When the non-evaporable water content change rate ΔL t When the water content is less than 0.01% / d, the cement-based material is considered to be completely hydrated. The non-evaporable water content at this time is the non-evaporable water content after complete hydration, which is recorded as L ∞ ;
[0026] Step 6: Calculate the hydration degree W of cement-based materials at time t using the following formula: s (t):
[0027]
[0028] Furthermore, the method for determining the volume expansion ratio P comprises the following steps:
[0029] Step 1: Take the above sieved samples and use the specific gravity bottle method to determine the specific gravity of the sieved samples at different curing ages, recorded as G t , t is the curing age (t=3, 7, 14, 28, 60, 90);
[0030] Step 2: The sieved sample consists of unhydrated cement-based materials and hydrated cement-based materials. The ratios of unhydrated cement-based materials and hydrated cement-based materials are calculated by the following formula: R an and R hp :
[0031]
[0032] In the formula, γ is the mass of cement-based material after complete hydration, and its value is equal to (1+L ∞ );
[0033] Step 3: Calculate the specific gravity G of the hydration product according to the following formula: sh :
[0034]
[0035] In the formula, G cd is the initial specific gravity of cement-based materials, measured by the pycnometer method;
[0036] Step 4: Calculate the volume expansion rate P of the cement-based material when it is fully hydrated according to the following formula:
[0037]
[0038] Furthermore, the initial porosity n0 is calculated using the following formula:
[0039]
[0040] Where V represents the total volume of solidified silt; m cd 、m s Respectively represent the mass of cement-based materials and silt in the solidified silt; G s Indicates the specific gravity of silt particles, measured by the pycnometer method; γ w ≈10kN / m 3 is the density of water, g≈10×10 3 kg·m / s 2 is the acceleration due to gravity.
[0041] Furthermore, the initial values of the fitting parameters y0, A, and B are -1000, 1000, and 0.1, respectively, and the correction steps are as follows:
[0042] Step 1: Take silt and cement-based materials from the construction site and prepare 6 groups of samples with different mix ratios or curing ages. After standard curing to the target age, carry out unconfined compressive strength test. The measured strength obtained in the test is recorded as q u,s ;
[0043] Step 2: Calculate the glue-to-air ratio GSR and predicted strength q of the five groups of samples with different ratios in step 1 u,y ;
[0044] Step 3: Compare the measured strength q u,s With the predicted strength q u,y, calculate the M value according to the following formula, and use the planning solution method to solve the minimum value of M, set the three coefficients y0, A, and B as variables, and solve and correct the three parameters:
[0045] M=∑(q u,s -q u,y (GSR) 2 .
[0046] This paper innovatively proposes the concept of GSR (Gelso-Void Ratio) of cement-based materials to quantify the strength characteristics of cement-based materials. On this basis, a prediction model based on GSR is proposed to accurately predict the unconfined compressive strength of cement-based materials. The GSR index combines the initial porosity n0, the curing agent dosage m cd , volume expansion rate P and hydration degree W s (t) and other key factors affecting the strength of solidified silt, providing a quantitative means to evaluate the synergistic effect of these factors on the unconfined compressive strength. The advantage of this prediction method is that it can accurately predict the unconfined compressive strength of cement-based material solidified silt without the need for preliminary tests to obtain fitting coefficients, significantly improving the professionalism and efficiency of the prediction process. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the method for constructing the prediction model in the present invention.
[0048] Figure 2 The comparison results of the measured strength, the preliminary predicted strength and the final predicted strength in Example 1 of the present invention are shown in FIG.
[0049] Figure 3 The comparison results of the measured strength, the preliminary predicted strength and the final predicted strength in Example 2 of the present invention are shown in FIG. DETAILED DESCRIPTION
[0050] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0051] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0052] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0053] Example 1
[0054] The soil sample used in Example 1 was taken from a subway construction site in Tianjin, a coastal city in northern China. The natural moisture content of the soil sample was measured on site to be 24.1%, and the specific gravity was G s The content of coarse particles (>75um) in the soil sample was 55.6%, the content of silt particles (5-75um) was 37.6%, and the content of clay particles (<5um) was 6.8%. The liquid limit, plastic limit and plasticity index of the soil sample were determined to be 32.5%, 27.2% and 5.3% respectively.
[0055] The cement-based material used is ordinary Portland cement (OPC, 42.5R / N), and the cement specific gravity is measured to be 3.11.
[0056] Step 1, mix 100g of cement and deionized water according to the standard consistency water amount for 180 seconds, pour the stirred slurry into a 200mL plastic bottle, cover and seal it, and place it in a 20°C environment for curing. When the sample reaches the specified age (3, 7, 14, 28, 60, 90 days), transfer the sample to 6 freeze-dried sample trays respectively, crush it after vacuum freeze-drying for 24 hours, and obtain powdered samples after passing through a 2mm sieve. Take 15g of powdered samples of different curing ages respectively, and use the specific gravity bottle method to determine the specific gravity of the sample; take 5g of powdered sample, place it in a muffle furnace at 1000°C and burn it for 2 hours, then take it out and place it in a dry environment to cool to room temperature, and determine the non-evaporable water content of the sample. The results of the determination of specific gravity and non-evaporable water content are shown in Table 1:
[0057] Table 1 Determination results of specific gravity and non-evaporable water content of Example 1
[0058] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Specific gravity G t > 2.43 2.26 2.13 2.07 2.03 1.96 Non-evaporable water content / % 7.02 11.02 13.14 15.59 15.87 17.57
[0059] Use function The non-evaporable water content L of cement-based materials at 6 curing ages t (t=3,7,14,28,60,90) are fitted to obtain L t Nonlinear function of curing age t;
[0060]
[0061] Find the derivative function ΔL with respect to the curing age t t , we can calculate that when ΔL t ≤0.01% / d when the curing age is t=105 days, at this time L t is equal to 17.48, then L ∞ Equal to 17.48.
[0062] Furthermore, the hydration degree W of cement-based materials at time t is calculated using the following formula: s (t), the results are shown in Table 2:
[0063]
[0064] Table 2 Hydration degree W of cement-based materials at different curing ages in Example 1 s (t) Calculation results
[0065] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Degree of hydration W s (t) / %]]> 40.15 63.04 75.18 89.20 90.78 100.00
[0066] Step 2: Calculate the ratio R of unhydrated cement-based materials to hydrated cement-based materials by the following formula: an and R hp , the results are shown in Table 3:
[0067]
[0068] In the formula, γ is the mass of cement-based material after complete hydration, and its value is equal to (1+L ∞ ).
[0069] Table 3 R in Example 1 an and R hp Calculation results
[0070] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[R an ]]> 0.56 0.33 0.22 0.09 0.08 0.00 <![CDATA[R hp ]]> 0.44 0.67 0.78 0.91 0.92 1.00
[0071] Further, the specific gravity G of the hydration product is calculated according to the following formula: sh , the results are shown in Table 4:
[0072]
[0073] In the formula, G cd It is the initial specific gravity of cement-based materials, measured by the pycnometer method.
[0074] Table 4 Specific gravity G of the hydration product in Example 1 sh Calculation results
[0075] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Specific gravity G sh > 1.90 1.99 1.96 2.00 1.97 1.96
[0076] Furthermore, the volume expansion rate P of the cement-based material when fully hydrated is calculated according to the following formula. The results are shown in Table 5. The average value of 186.1% is taken as the volume expansion rate P of the cement-based material.
[0077]
[0078] Table 5 Calculation results of volume expansion ratio P in Example 1
[0079] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days Volume expansion rate P 192 184 187 182 185 187
[0080] Step 3, take 138.5g of dried soil sample (drying moisture content is 1.4%), add 33g of deionized water, stir for 5min, put into a sealed plastic bag and let stand for 24h. Weigh 8.5g of cement and add it to the wet soil and stir thoroughly to ensure uniformity. Press the mixture into a cylindrical mold with a diameter of 50mm and a height of 50mm. After demolding, seal with plastic film to prevent moisture loss, and prepare 5 more samples in the same way. The samples were placed in a curing room (temperature 20±2℃, humidity 95%) and cured for 3, 7, 14, 28, 60, and 90 days, and then the unconfined compressive strength test was carried out. The results are shown in Table 6:
[0081] Table 6 Unconfined compressive strength of solidified silt in Example 1
[0082] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Measured strength q u,s / kPa]]> 249.30 380.07 488.02 653.06 783.70 828.93
[0083] The initial porosity n0 of the solidified silt is calculated to be 44.87% using the following formula.
[0084]
[0085] Where V is equal to the volume of the cylindrical test block, which is 98.175 cm 3 .
[0086] Furthermore, the following formula was used to calculate the gel-spatter ratio GSR of the solidified silt, and the results are shown in Table 7:
[0087]
[0088] Table 7 Solidified clay glue-air ratio GSR in Example 1
[0089] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days GSR / % 1.96 3.08 3.69 4.38 4.46 4.94
[0090] Step 4: Use the following formula to make a preliminary prediction of the unconfined compressive strength of cement-based material-solidified silt:
[0091] q u,y =y0+A×e Bx
[0092] In the formula, y0, A, and B are fitting parameters, and their initial values are -1000, 1000, and 0.1 respectively; q u,y represents the preliminary prediction result of the unconfined compressive strength of the solidified silt, and x represents the gel-spatial ratio GSR of the solidified silt.
[0093] Table 8 Preliminary prediction results of unconfined compressive strength of solidified silt in Example 1
[0094] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Predicted strength q u,y / kPa]]> 216.52 360.70 446.28 549.60 562.05 638.85
[0095] Furthermore, compared with the measured intensity q u,sWith the predicted strength q u,y , calculate the M value according to the following formula, and use the planning solution method to solve the minimum value of M, set the three coefficients y0, A, and B as variables, solve and correct the three parameters, and get the corrected y0, A, and B as -49.64, 135.67, and 0.384:
[0096] M=∑(q u,s -q u,y (GSR) 2
[0097] The modified fitting parameters y0, A, and B are substituted into the above formula as a prediction method for the unconfined compressive strength of cement-based material-solidified silt in this project, providing a basis for engineering design and construction control.
[0098] Example 2
[0099] The soil sample used in Example 2 was taken from a subway construction site in Tianjin, a coastal city in northern China. The natural moisture content of the soil sample was measured on site to be 24.1%, and the specific gravity was G s The content of coarse particles (>75um) in the soil sample was 55.6%, the content of silt particles (5-75um) was 37.6%, and the content of clay particles (<5um) was 6.8%. The liquid limit, plastic limit and plasticity index of the soil sample were determined to be 32.5%, 27.2% and 5.3% respectively.
[0100] The cement used was ordinary Portland cement (OPC, 42.5R / N). The phosphogypsum came from a chemical plant in Luhe District, Nanjing, Jiangsu. The specific gravity of cement and phosphogypsum was measured to be 3.11 and 3.01 respectively.
[0101] 83.33g cement and 16.67g phosphogypsum were fully mixed, deionized water according to the standard consistency was added and mixed for 180 seconds, the mixed slurry was poured into a 200mL plastic bottle, sealed with a cover, and placed in a 20°C environment for curing. When the samples reached the specified age (3, 7, 14, 28, 60, 90 days), the samples were transferred to 6 freeze-dried sample trays, crushed after vacuum freeze drying for 24 hours, and powdered samples were obtained after 2mm sieve. 15g powdered samples of different curing ages were taken respectively, and the specific gravity of the samples was determined by the specific gravity bottle method; 5g powdered samples were taken, placed in a muffle furnace at 1000°C for 2 hours, and then taken out and placed in a dry environment to cool to room temperature, and the non-evaporable water content of the samples was determined. The results of the determination of specific gravity and non-evaporable water content are shown in Table 9:
[0102] Table 9 Determination results of specific gravity and non-evaporable water content of Example 2
[0103] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Specific gravity G t > 2.32 2.14 2.03 1.96 1.92 1.87 Non-evaporable water content / % 8.10 13.08 14.94 18.10 21.01 24.62
[0104] Use function The non-evaporable water content L of cement-based materials at 6 curing ages t (t=3,7,14,28,60,90) are fitted to obtain L t Nonlinear function of curing age t;
[0105]
[0106] Find the derivative function ΔL with respect to the curing age t t , we can calculate that when ΔL t ≤0.01% / d when the curing age is t=390 days, at this time L t is equal to 30.86, then L ∞ Equal to 30.86.
[0107] Furthermore, the hydration degree W of cement-based materials at time t is calculated using the following formula: s (t), the results are shown in Table 10:
[0108]
[0109] Table 10 Hydration degree W of cement-based materials at different curing ages in Example 2 s (t) Calculation results
[0110] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Degree of hydration W s (t) / %]]> 26.26 42.37 48.41 58.65 68.09 79.79
[0111] Furthermore, the ratio R of unhydrated cement-based materials to hydrated cement-based materials is calculated by the following formula: an and R hp , the results are shown in Table 11:
[0112]
[0113] In the formula, γ is the mass of cement-based material after complete hydration, and its value is equal to (1+L ∞ ).
[0114] Table 11 R in Example 2 an and R hp Calculation results
[0115] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[R an ]]> 0.68 0.51 0.45 0.35 0.26 0.16 <![CDATA[R hp ]]> 0.32 0.49 0.55 0.65 0.74 0.84
[0116] Further, the specific gravity G of the hydration product is calculated according to the following formula: sh , the results are shown in Table 12:
[0117]
[0118] In the formula, G cd It is the initial specific gravity of cement-based materials, measured by the pycnometer method.
[0119] Table 12 Specific gravity G of the hydration product in Example 2 sh Calculation results
[0120] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Specific gravity G sh > 1.57 1.65 1.61 1.65 1.70 1.75
[0121] Furthermore, the volume expansion rate P of the cement-based material when fully hydrated was calculated according to the following formula. The results are shown in Table 13, and the average value of 236.9% is taken as the volume expansion rate P of the cement-based material.
[0122]
[0123] Table 13 Calculation results of volume expansion ratio P in Example 2
[0124] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days Volume expansion rate P 249 237 243 237 231 224
[0125] Take 968g of dried soil sample (drying moisture content is 1.4%), add 226g of deionized water, stir for 5min, put into a sealed plastic bag and let stand for 24h. Weigh 58g of cement and 11.6g of phosphogypsum, add to the wet soil and stir thoroughly to ensure uniformity. Press 170g, 175g, 180g, 185g, 190g and 195g of the mixture into a cylindrical mold with a diameter of 50mm and a height of 50mm respectively. After demolding, seal with plastic film to prevent moisture loss. Place the sample in a curing room (temperature 20±2℃, humidity 95%) for 28 days and then conduct an unconfined compressive strength test. The results are shown in Table 14:
[0126] Table 14 Unconfined compressive strength of solidified silt in Example 2
[0127] Specimen weight 170g 175g 180g 185g 190g 195g <![CDATA[Measured strength q u,s / kPa]]> 698.84 863.94 967.64 1008.37 1101.88 1251.56
[0128] The initial porosity n0 of the solidified silt is calculated using the following formula, and the results are shown in Table 15:
[0129]
[0130] Where V is equal to the volume of the cylindrical test block, which is 98.175 cm 3 .
[0131] Table 15 Initial porosity of solidified silt in Example 2
[0132] Specimen weight 170g 175g 180g 185g 190g 195g <![CDATA[Initial porosity n0 / %]]> 47.53 45.89 44.36 42.97 41.38 40.02
[0133] Furthermore, the following formula was used to calculate the gel-spatter ratio GSR of the solidified silt, and the results are shown in Table 16:
[0134]
[0135] Table 16 Solidified clay glue-air ratio GSR in Example 8
[0136] Specimen weight 170g 175g 180g 185g 190g 195g GSR / % 5.21 5.56 5.92 6.26 6.68 7.07
[0137] Furthermore, the following formula is used to make a preliminary prediction of the unconfined compressive strength of silt solidified by cement-based materials:
[0138] q u,y =y0+A×e Bx
[0139] In the formula, y0, A, and B are fitting parameters, and their initial values are -1000, 1000, and 0.1 respectively; q u,y represents the preliminary prediction result of the unconfined compressive strength of the solidified silt, and x represents the gel-spatial ratio GSR of the solidified silt.
[0140] Table 17 Preliminary prediction results of unconfined compressive strength of solidified silt in Example 1
[0141] Maintenance age 3 days 7 days 14 days 28 days 60 days 90 days <![CDATA[Predicted strength q u,y / kPa]]> 683.71 743.68 807.60 870.12 950.33 1027.90
[0142] Furthermore, compared with the measured intensity q u,s With the predicted strength q u,y , calculate the M value according to the following formula, and use the planning solution method to solve the minimum value of M, set the three coefficients y0, A, and B as variables, solve and correct the three parameters, and get the corrected y0, A, and B as -1750, 1380, and 0.11:
[0143] M=∑(q u,s -q u,y (GSR) 2
[0144] The modified fitting parameters y0, A, and B are substituted into the above formula as a prediction method for the unconfined compressive strength of cement-based material-solidified silt in this project, providing a basis for engineering design and construction control.
Claims
1. A method for predicting the strength of cement-solidified silt based on the ratio of cement to air, characterized in that: The following steps are involved: Step 1, measuring the specific gravity of silt and cement-based curing agent, and calculating the initial porosity; Step 2, conducting indoor experiments to determine the hydration degree of the cement-based curing agent at different curing ages and calculating the volume expansion rate of the cement-based curing agent; Step 3, calculating the cement-solidified silt-soil ratio at different curing ages through initial porosity, hydration degree and volume expansion rate; Step 4, substituting the cement-air ratio into the strength prediction model to predict the unconfined compressive strength of cement-solidified silt at different curing ages; The prediction model is shown as follows: q u =y0+A×e Bx In the formula, y0, A, B are fitting parameters, q u represents the unconfined compressive strength of the solidified silt, and x represents the gel-spatial ratio GSR of the solidified silt; The calculation formula of the glue-to-air ratio GSR is as follows: In the formula, m cd , W s (t), P and G cd are the amount of cement-based materials added, hydration degree, volume expansion rate and specific gravity; g is the acceleration of gravity; n0 and V are the initial porosity and volume of the solidified silt, γ w The weight of water.
2. The method according to claim 1, characterized in that The degree of hydration W s The determination method of (t) comprises the following steps: Step 1: Mix the cement-based material with water according to the standard consistency and place it under standard curing conditions for 3, 7, 14, 28, 60 and 90 days; Step 2: taking out the cement-based material that has reached the curing age, freeze-drying, crushing, and passing through a 2 mm sieve to obtain a sieved sample; Step 3: Take 5g of sieved samples of different curing ages, place them in a muffle furnace at 1000℃ for 2 hours, cool them in a dry environment, and weigh the sample mass, recorded as m t , t is the curing age, then the weight of non-evaporated water of cement-based materials at time t is (5-m t ), the non-evaporable water content of cement-based materials at time t is defined as L t , calculated using the following formula: Step 4: Use the function shown in the following formula to calculate the non-evaporable water content L of cement-based materials at 6 curing ages. t Fitting is performed to obtain L t Regarding the nonlinear function of the curing age t, Step 5: Use step 4 to get L t Regarding the nonlinear function of curing age t, the non-evaporable water content of cement-based materials when fully hydrated is predicted. When the non-evaporable water content change rate ΔL t When the water content is less than 0.01% / d, the cement-based material is considered to be completely hydrated. The non-evaporable water content at this time is the non-evaporable water content after complete hydration, which is recorded as L ∞ ; Step 6: Calculate the hydration degree W of cement-based materials at time t using the following formula: s (t):
3. The method according to claim 2, characterized in that The method for determining the volume expansion rate P comprises the following steps: Step 1: Take the above sieved samples and use the specific gravity bottle method to determine the specific gravity of the sieved samples at different curing ages, recorded as G t , t is the curing age; Step 2: The sieved sample consists of unhydrated cement-based materials and hydrated cement-based materials. The ratios of unhydrated cement-based materials and hydrated cement-based materials are calculated by the following formula: R an and R hp : Where γ is the mass of cement-based material after complete hydration, and its value is equal to (1+L ∞ ); Step 3: Calculate the specific gravity G of the hydration product according to the following formula: sh : In the formula, G cd is the initial specific gravity of cement-based materials, measured by the pycnometer method; Step 4: Calculate the volume expansion rate P of the cement-based material when it is fully hydrated according to the following formula:
4. The method according to claim 3, characterized in that: The initial porosity n0 is calculated using the following formula: Where V represents the total volume of solidified silt; m cd 、m s Respectively represent the mass of cement-based materials and silt in the solidified silt; G s Indicates the specific gravity of silt particles, measured by the pycnometer method; γ w ≈10kN / m 3 , g≈10×10 3 kg·m / s 2 .
5. The method according to claim 4, characterized in that The initial values of the fitting parameters y0, A, and B are -1000, 1000, and 0.1 respectively, and the correction steps are as follows: Step 1: Take silt and cement-based materials from the construction site and prepare 6 groups of samples with different mix ratios or curing ages. After standard curing to the target age, carry out unconfined compressive strength test. The measured strength obtained in the test is recorded as q u,s ; Step 2: Calculate the glue-to-air ratio GSR and predicted strength q of the five groups of samples with different ratios in step 1 u,y ; Step 3: Compare the measured strength q u,s With the predicted strength q u,y , calculate the M value according to the following formula, and use the planning solution method to solve the minimum value of M, set the three coefficients y0, A, and B as variables, and solve and correct the three parameters: M=∑(q u,s -q u,y (GSR)) 2 。
Citation Information
Patent Citations
Building structure concrete form stripping strength digital prediction method
CN114818089A
Digital evaluation method for concrete strength
CN114993826A
Strength estimation method and strength estimation system of soil cement
JP2022112314A